A comparison of migrant and resident bird population changes in South Africa using citizen science data: trends in relation to Northern Hemisphere distribution. (28th October 2022) - Lee, Alan TK; Hammer, Sophie AJ
Abstract : Many species of migratory birds have been declining on the Palearctic-African flyways in recent decades due to human population pressure and land-use intensification. Models predict that the declining trends of migratory birds will continue into the foreseeable future across much of Africa, likely exacerbated by climate change. While sub-Saharan Africa is viewed as less important for these migrants than the Sahel, the region still receives many migrant species. We use the citizen science Southern African Bird Atlas Project data sets (SABAP1 and SABAP2) to determine relative change between atlas periods (1987–1991; 2007–2021). Firstly, we validate our metrics of population change on a dataset of 581 species that occur frequently in South Africa, Lesotho and Eswatini by examining change in relation to migratory status (Palearctic, Intra-Africa or Resident) and other species' traits. We found greatest declines in migrants but with magnitudes not as great as expected, with largest relative decreases for Palearctic migrants, and little difference between Intra-Africa migrants and residents. Declines were best described by size independent of migratory status, even when controlling for phylogeny. For the set of Palearctic migrants, we then examine if change is related to Northern Hemisphere distribution. We found greater decreases for birds with breeding grounds in southern Asia (India and south-eastern Asia) relative to Europe. These results are useful for conservation agencies wishing to extend ties to relevant researchers and conservationists in these regions, and highlights potential challenge areas for this set of birds on their breeding grounds.